ANALISIS PEMILIHAN MODA TRANSPORTASI DARAT ANTARA KERETA API DAN BUS PADA RUTE CIANJUR-SUKABUMI - salsabila, Salwa; Setiawan, Devi (Universitas Pendidikan Indonesia (UPI), 2025)
The choice of transportation mode on the Cianjur-Sukabumi route is influenced by various factors, including travel costs, travel time, comfort, accessibility, and personal preferences. This study aims to analyze the factors affecting passengers’ decisions when choosing between trains and buses and to identify the dominant mode used. This research employs a quantitative survey method, collecting data through questionnaires from 174 respondents. Additionally, direct observations were conducted to assess the actual service conditions of both transport modes. The data were analyzed using the Binary Logit Difference Model and the Binary Logit Ratio Model to measure the probability of mode selection based on influencing independent variables. he findings reveal that most respondents prefer trains (56.9%) over buses (43.1%). The primary reason for choosing trains is the lower travel cost (36.4%), while bus users prioritize comfort and flexible departure schedules (38.7%). The Binary Logit Difference Model analysis indicates that as the cost gap between trains and buses increases, the likelihood of choosing the train also rises. Meanwhile, the Binary Logit Ratio Model demonstrates a positive correlation between the cost ratio and the probability of mode selection. These findings provide valuable insights for policymakers and transport operators to enhance public transportation services. Recommendations include optimizing train schedules, improving bus comfort facilities, and adjusting fares to remain competitive. Understanding passenger preferences can help implement more effective transport policies and improve service quality on the Cianjur-Sukabumi route. Keywords: Binary Logit, Bus, Cianjur-Sukabumi, Quantitative Analysis, Train, Transportation Mode Choice.